Evaluating TCP BBRv3 performance in wired broadband networks - Gomez, Jose; Kfoury, Elie F.; Crichigno, Jorge; Srivastava, Gautam (Computer communications, 2024)
Introduced by Google in 2016, the first version of the Bottleneck Bandwidth and Round-Trip Time (BBRv1) congestion control algorithm (CCA) marked a significant advancement in network communication. Unlike traditional loss-based CCAs such as CUBIC and Reno, BBRv1 focused on balancing throughput and delay without relying on packet losses as a congestion signal. However, BBRv1 faced fairness issues due to its aggressiveness when interacting with loss-based CCAs. To address this issue, BBRv2 was developed, incorporating multiple metrics to improve fairness with loss-based CCAs. Despite improvements, BBRv2 encountered bugs and performance limitations, prompting the release of BBRv3 in 2023. BBRv3 addressed bugs found in BBRv2 and fine-tuned parameters to enhance flow coexistence. This paper evaluates the performance of BBRv3 across diverse network scenarios by comparing it with CUBIC and further contrasts this comparison with those involving CUBIC against BBRv2 and BBRv1. The evaluation explores BBRv3’s behavior under different conditions, considering variations in the number of flows, propagation delays, loss rates, and buffer sizes. Additionally, this paper explores the influence of Active Queue Management (AQM) algorithms in addressing the RTT unfairness issue. The results indicate that BBRv3’s coexistence with CUBIC is comparable to that observed in BBRv2, and it depends on factors such as buffer size and the number of flows. BBRv3 maintains high throughput and lower retransmissions at 1% loss rates compared to its predecessors. Moreover, BBRv3 consistently keeps low queue occupancy and achieves low Flow Completion Times (FCTs) in scenarios with short and long flows, even with large buffer sizes.